Hept-1-yne partial hydrogenation reaction over supported Pd and W catalysts - Lederhos, Cecilia Rosa (2011)
In order to increase the production of olefins the partial hydrogenation of alkynes has achieved industrial importance. In this sense catalysts with selective hydrogenation properties may be of potential interest. In this work mono and bimetallic Pd and W catalysts supported on γ-alumina with low metal content (2.4% W and 0.4% Pd) were prepared. XPS, XRD, TPR and hydrogen chemisorption techniques were used for the characterization. The effect of metallic precursor incorporation order and of the reduction temperature, on the activity and selectivity for the partial hydrogenation of hept-1-yne at mild reaction conditions, were evaluated. Low-loaded palladium monometallic catalyst showed a high selectivity but it was the least active. Moreover, bimetallic catalysts proved to be more active than the classical Lindlar catalyst. The addition of Pd to the W/γ-Al2O3 catalyst greatly improved the total conversion and the selectivity to the desired product. XPS results suggest electronic effects between Pd and W metals. The bimetallic W-Pd catalyst treated in hydrogen at low temperature conditions (393 K) showed the highest activity and selectivity values. © 2011 Elsevier B.V. All rights reserved.